Ultra-high-throughput screening of beta glucoside kinase random mutagenesis library for phosphorus-sulfur bond Formation - Ibrahim Ali, Noorbatcha; Hamzah, Mohd. Salleh (2017)
Abstract. In the continual quest of novel biocatalysts with improved properties that will fulfil the raising industrial demands, directed evolution appears to be one of the most powerful tools in generating novel enzymes. Error -Prone PCR is a customized PCR protocol that will randomly introduce mutations creating a variant library. Beta glucoside kinase (bglk) is an enzyme that catalyzes the phosphor transformation to the 6’ C in a glucose molecule. The aim of the presented research is to engineer the bglk enzyme for phosphorus-sulfur bond formation. Two bglk libraries were created, one with a low mutation rate (0-4 mutation/kb) and the second with high mutation rate (9-16 mutation/kb) and was screened with Fluorescent Activated Cell Sorting (FACS) using a 6’thio-glucose-BODIPY as fluorescent substrate. Prior to this, a Glucose-BODIPY substrate was used with the wild type enzyme in order to test the cell incubation conditions with the fluorescent substrate. The positive clones collected from these two libraries, will be sequenced to verify the type and location of the mutations.